Pengaruh positive thinking dalam meningkatkan self acceptance pada siswa - Baiq Hardianti; Ahmad Munjirin (Universitas Muhammadiyah Malang, 2024)
This study is motivated by the researcher’s attention to class XII MA NWDI Sakra students who have low self-acceptance.So this study aims to determine the effect of positive thinking in increasing the self-acceptance of class XII MA NWDISakra students. This research was conducted at MA NWDI Sakra with a population of 63 students and the sample usedwas as many as the population, namely 63 students because the population was less than 100. This study shows thatthe Kolmogorov Smirnov calculation obtained p = 0.200¿ 0.05 which means that the data distribution has been normallydistributed so that data analysis with the t-test (Paired Sample t-test) can be done using the help of SPSS version 25.The results of this study state that positive thinking affects increasing self-acceptance in class XII MA NWDI Sakrastudents.